Respuesta :
Simplifying
x4 + -2x3 + 6x2 + -2x = 5
Reorder the terms:
-2x + 6x2 + -2x3 + x4 = 5
Solving
-2x + 6x2 + -2x3 + x4 = 5
Solving for variable 'x'.
Reorder the terms:
-5 + -2x + 6x2 + -2x3 + x4 = 5 + -5
Combine like terms:
5 + -5 = 0 -5 + -2x + 6x2 + -2x3 + x4 = 0
The solution to this equation could not be determined
x4 + -2x3 + 6x2 + -2x = 5
Reorder the terms:
-2x + 6x2 + -2x3 + x4 = 5
Solving
-2x + 6x2 + -2x3 + x4 = 5
Solving for variable 'x'.
Reorder the terms:
-5 + -2x + 6x2 + -2x3 + x4 = 5 + -5
Combine like terms:
5 + -5 = 0 -5 + -2x + 6x2 + -2x3 + x4 = 0
The solution to this equation could not be determined
[tex]2x^3 + 6x^2 -2x - 5[/tex]
by x+3 , negative -3
-3
|2 |6 |-2 |-5|
|2 |0 |-2 |1 |
[tex]2x^2+0x-2+(r1)=2x^2-2+\frac{1}{x+3}[/tex]
[tex]\frac{2x^3 + 6x^2 -2x - 5}{x+3}=2x^2-2+\frac{1}{x+3}[/tex]
by x+3 , negative -3
-3
|2 |6 |-2 |-5|
|2 |0 |-2 |1 |
[tex]2x^2+0x-2+(r1)=2x^2-2+\frac{1}{x+3}[/tex]
[tex]\frac{2x^3 + 6x^2 -2x - 5}{x+3}=2x^2-2+\frac{1}{x+3}[/tex]